Fundamental processes in ecology an earth systems approach - Wilkinson, David M. 1963- (Oxford University Press, 2006)
"Fundamental Processes in Ecology presents a way to study ecosystems that is not yet available in ecology textbooks but is resonant with current thinking in the emerging fields of geobiology and Earth System Science. It provides an alternative, process-based classification of ecology and proposes a truly planetary view of ecological science. To achieve this, it asks (and endeavours to answer) the question, 'what are the fundamental ecological processes which would be found on any planet with Earth-like, carbon based, life?'"--BOOK JACKET.